2018
DOI: 10.1101/375311
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cancerous phenotypes associated with hypoxia-inducible factors are not influenced by the volatile anesthetic isoflurane in renal cell carcinoma

Abstract: Cancerous phenotypes associated with hypoxia-inducible factors are not influenced by the volatile anesthetic isoflurane in renal cell carcinoma Hypoxia-inducible factors are not activated by isoflurane Abstract The possibility that anesthesia during cancer surgery may affect cancer recurrence, metastasis, and patient prognosis has become one of the most important topics of interest in cancer treatment. For example, the volatile anesthetic isoflurane was reported in several studies to induce hypoxia-inducible f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
4
2
Order By: Relevance
“…Supporting HIF2α involvement in ccRCC migration, RCC4 VHL cells migrated more than RCC4 WT, in contrast to previous publications 33,34 . In this case, as they also express HIF1α, both HIF2α and HIF1α could be inhibiting cell migration; however, treatment with PT2385 generated an intermediate phenotype pointing to a more important role of HIF2α.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Supporting HIF2α involvement in ccRCC migration, RCC4 VHL cells migrated more than RCC4 WT, in contrast to previous publications 33,34 . In this case, as they also express HIF1α, both HIF2α and HIF1α could be inhibiting cell migration; however, treatment with PT2385 generated an intermediate phenotype pointing to a more important role of HIF2α.…”
Section: Discussioncontrasting
confidence: 91%
“…On the other hand, PT2385 treatment showed that DNA binding is not completely abolished by the inhibitor, as previously reported 22 , as cell invasion was not 100% suppressed. Supporting HIF2α involvement in ccRCC migration, RCC4 VHL cells migrated more than RCC4 WT, in contrast to previous publications 33,34 . In this case, as they also express HIF1α, both HIF2α and HIF1α could be inhibiting cell migration; however, treatment with PT2385 generated an intermediate phenotype pointing to a more important role of HIF2α.…”
Section: Discussioncontrasting
confidence: 91%
“…Total RNA was processed with a TruSeq Stranded mRNA sample prep kit (Illumina, San Diego, CA, USA) (Sumi et al, 2019). Poly(A) RNA libraries were then constructed using the TruSeq Stranded mRNA library preparation kit (Illumina) and sequenced in 100-bp paired-end reads on an Illumina NovaSeq6000 platform (Sumi et al, 2019). RNA-Seq was performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…29 . Poly(A) RNA libraries were then constructed using the TruSeq Stranded mRNA www.nature.com/scientificreports/ library preparation kit (Illumina) and sequenced in 100-bp paired-end reads on an Illumina NovaSeq6000 platform 30 . RNA-Seq was performed in triplicate.…”
Section: Quantitative Reverse Transcription-polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%